Identifikasi Keberadaan Jamur Udara dan Karakteristik Suhu, Kelembaban, dan Pencahayaan Ruangan di Puskesmas Panjatan II - Yuliana Hartina; Monika Puti Solikah; Novita Eka Putri (Syntax Corporation Indonesia, 2024)
Microorganisms in a room’s air are organisms that are carried by the air in the form of spores through air ventilation or people entering the room. Pathogenic fungi can spread and enter the human body which can cause infection. Laboratory studies explain that there are factors that can help fungal growth such as temperature, humidity and lighting. This research aims to identify the presence and types of airborne fungi and the characteristics of temperature, humidity and room lighting at the Panjatan II Community Health Center. This research method is experimental with a quantitative descriptive approach and the sample size of this research is 15 samples that was taken with a purposive sampling technique. The instruments used in this research were a hygrometer, luxmeter, PDA media, and LPCB staining. This research used a statistical application, namely SPSS to do a data processing and descriptive analysis which aims to see the characteristics of humidity, humidity and room lighting at the Panjatan II Community Health Center. This research found that there were airborne fungi like Aspergillus sp., and Candidia sp from 15 room samples in the media. In addition, the measurement results of temperature, humidity, and room lighting at the Panjatan II Community Health Center were 29-32°C temperatures, 65-69% humidity, and 70-160 Lux lighting. The conclusion of this research is that the type of fungus found in the Panjatan II Community Health Center room is a type of pathogenic fungus which consists of Aspergillus sp., and Candidia sp. The characteristics of room measurements on temperature, humidity and lighting characteristics exceed the standard requirements for air physical quality according to Minister of Health Regulation No. 2 of 2023.